THE PROVISION OF TEENAGER’S SELF–ESTEEM ISSUE IN THE MODERN PSYCHOLOGY - MKRTUMYAN, MELS; GEVORGYAN, ANNA (Main Issues Of Pedagogy And Psychology, 2013)
The problem of self–esteem is discussed in the article. It is stated as the most modern and researched issue in the Modern Psychology. It is also spoken about the issue of the individual self–esteem of and transformations of demonstrated self–esteem of the teenager.